2020
DOI: 10.1007/978-3-030-49864-1_1
|View full text |Cite
|
Sign up to set email alerts
|

Lectures on the Ax–Schanuel conjecture

Abstract: We prove that for every Shimura variety S, there is an integral model S such that all CM points of S have good reduction with respect to S. In other words, every CM point is contained in SpZq. This follows from a stronger local result wherein we characterize the points of S with potentially-good reduction (with respect to some auxiliary prime ℓ) as being those that extend to integral points of S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…For the type II string such theories can be obtained by compactifying on Calabi-Yau three-folds in the presence of fluxes, where the choice of fluxes is constrained by the tadpole cancellation condition (for a review see for instance [5]). Remarkably, using this tadpole condition it has been argued that for a given compactification manifold the number of flux vacua is finite [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…For the type II string such theories can be obtained by compactifying on Calabi-Yau three-folds in the presence of fluxes, where the choice of fluxes is constrained by the tadpole cancellation condition (for a review see for instance [5]). Remarkably, using this tadpole condition it has been argued that for a given compactification manifold the number of flux vacua is finite [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…These are motivated by Lawrence-Venkatesh's recent breakthrough on the non-density of integral points on the moduli space of hypersurfaces [61], and are in accordance with Lang-Vojta's conjecture for affine varieties. Our results in this section are proven using methods from Hodge theory, and are loosely related to Bakker-Tsimerman's chapter in this book [11].…”
Section: Introductionmentioning
confidence: 57%
“…Namely, in [50] it is shown that a complex algebraic variety with a quasi-finite period map is geometrically hyperbolic. For other results about period domains we refer the reader to the article of Bakker-Tsimerman in this book [11].…”
Section: Hyperbolicity Along Field Extensionsmentioning
confidence: 99%
“…Let us also comment on the linear scenario in the context of the general finiteness theorems for flux vacua satisfying the self-duality condition [38,63]. A first observation is that the tadpole N flux = −e L m L seems to be independent of the flux e α .…”
Section: Relations To Swampland Conjectures and Finiteness Theoremmentioning
confidence: 99%
“…This implies that if one aims to describe the structure of all flux vacua one has to leave the world of algebraic geometry. Remarkably, a delicate and powerful extension of algebraic geometry that can be use to describe flux vacua is provided by using tame topology and o-minimality [63]. The resulting tame form of geometry manifest the notion of finiteness and removes many pathologies that are allowed in geometric settings based on ordinary topology.…”
Section: Relations To Swampland Conjectures and Finiteness Theoremmentioning
confidence: 99%